Endothelial Activation in Orientia tsutsugamushi Infection Is Mediated by Cytokine Secretion From Infected Monocytes - Tantibhedhyangkul, Wiwit; Matamnan, Sutthicha; Longkunan, Asma; Boonwong, Chawikan; Khowawisetsut, Ladawan (Frontiers in Cellular and Infection Microbiology, 2021)
Scrub typhus, caused by Orientia tsutsugamushi, is a common systemic infection in Asia. Delay in diagnosis and treatment can lead to vasculitis in the visceral organs and other complications. The mechanisms that drive endothelial activation and the inflammatory response in O. tsutsugamushi infection remain unknown. In addition, the interaction between monocytes and endothelial cells is still unclear. Here we demonstrate that O. tsutsugamushi-infected human dermal microvascular endothelial cells produced moderate levels of chemokines and low levels of IL-6 and IFN-β, but not TNF or IL-1β. Recombinant TNF and cytokine-rich supernatants from infected monocytes markedly enhanced chemokine production in infected endothelial cells. We also show that TNF and monocyte supernatants, but not O. tsutsugamushi infection of endothelial cells per se, upregulated the endothelial cell surface expression of ICAM-1, E-selectin, and tissue factor. This finding was consistent with the inability of O. tsutsugamushi to induce cytokine secretion from endothelial cells. The upregulation of surface molecules after stimulation with monocyte supernatants was significantly reduced by neutralizing anti-TNF antibodies. These results suggest that endothelial cell activation and response are mainly mediated by inflammatory cytokines secreted from monocytes.